Legalisation and Liberalisation of Cannabis: The Benefits and Drawbacks of the Global Trend - Fasesan OA (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2023)
Cannabis sativa is a complex domesticated plant that has an unstable taxonomy. It is the most utilised illicit substance that has gained prominence in some parts of the world as it is used for therapeutic and recreational purposes. C. Sativa has also been used to manage numerous medical conditions since antiquity. The pharmacological benefits of C. sativa are still subject to intense research due to inconsistent outcomes. C. sativa, like other psychoactive substances, has both medical and psychological side effects. Despite the lack of knowledge, medical practitioners continue to recommend this substance. This review aims to highlight the effects of legalisation and liberalisation on the global trend of cannabis use. A search was conducted on Google Scholar and Medline from 2012 to date. The results showed that cannabis was found to be effective in the management of some medical conditions, though more work is required. Recreational use is rising due to a reduced perception of harm and the availability of more potent species. Cannabis use persists despite the several medical and psychological side effects. It is concluded that there is a shortage of information on the safety and pharmacological properties of C. sativa, and more work is required.